CD24+ MDSC-DCs Induced by CCL5-Deficiency Showed Improved Antitumor Activity as Tumor Vaccines - Huang, Lei; Ding, Zequn; Zhang, Yan (Global Medical Genetics, 2022)
Background Dendritic cell (DC) tumor vaccine has been extensively utilized in preclinical and clinical studies; however, this technique has encountered many difficulties, particularly in late-stage tumor patients. For those, ex vivo-induced DCs are actuallymyeloid-derived suppressive cells-derived DCs (MDSC-DCs). MDSCs with immunosuppressive activity, but not monocytes, became the major DC precursor. Thus, how to enhance antitumor activity of MDSC-DCs is urgent need to address.Methods We utilized 4T1 and MC38 tumor-bearing both wildtype and CC chemokine ligand 5−/− (CCL5−/−) mice as animal models. MDSC-DCs were induced from splenocytes of these mice by granulocyte macrophage–colony stimulating factor/interleukin-4 with or without all-trans-retinoic acid (ATRA) in vitro for 7 days, then incubated with tumor-cell-lysis to treat mouse models for total three doses. For human MDSC-DCs, peripheral bloods from colorectal cancer patients were induced in vitro as murine cells with or without T- lymphocytes depletion to get rid of CCL5.Results Flow cytometry analysis showed that MDSCs from CCL5−/− mice could be induced into a new type of CD24+ MDSC-DCs in the presence of ATRA, which had more antitumor activity than control. Antibody blocking and adoptive transfer experiments demonstrated that downregulation of regulatory T cells (Tregs) mediated the inhibition of CD24+ MDSC-DCs on tumor growth. Mechanically, CD24+ MDSC-DCs inhibited Tregs' polarization by secreting cytokine or coactivators' expression. What's important, decreasing CCL5 protein levels by T- lymphocytes depletion during both murine and human MDSC-DCs in vitro induction could also acquire CD24+ MDSC-DCs.Conclusion Knockdown of CCL5 protein during MDSC-DCs culture might provide a promising method to acquire DC-based tumor vaccines with high antitumor activity.
Keywords: CD24+ MDSC-DCs; CCL5-deficiency; tumor vaccines; antitumor activity; Tregs